Effect of vitamin D supplementation on the methylation status of the SLC30A10 gene on colon cancer cell lines (Journal of the College of Basic Education, 2024)
Background: Overall, colorectal cancer is the third most common cancer and the second most lethal after breast and lung cancer. The association of cancers with expression of the Brexit gene is not covered. Methylation is a subtype of epigenetics and can therefore be altered by methyl receptors or donor drugs. According to recent studies, the SLC30A10 gene is hyper methylated in colorectal cancer and shows decreased expression. On the other hand, many studies have been conducted on the epigenetic effect of vitamin D on various genes responsible for various diseases and cancers. Therefore, in this study, we aimed to study the epigenetic effect of this substance in colorectal cancer cell lines SW48 and HT29 on the methylation of this gene.Method: First, the amount of vitamin D was in the range of 0 to 250 mg of vitamin D after 24 hours and the IC50 was calculated to be 95 mg/ml. Cells were treated with DMEM and RPMI medium for 24 h at 37°C, 5% CO supplemented with 25 mg/ml vitamin D. After DNA extraction and quality and quantity tests, the samples were bisulfate. Finally, the methylation status of the samples was assessed using specific primers and real-time PCR.Results: The results showed that a dose of 95 mg of vitamin D on HT29 cells at a significant level (P value < 0.05) reduces methylation of the SLC30A10 gene.Conclusion: It is hoped that this finding will shed light on a new treatment for colon cancer. However, the introduction of vitamin D as an effective pharmacological supplement for CRC requires further studies. It is recommended to study the epigenetic effects of vitamin D on other key genes in colon cancer such as APC, TP53, KRAS, NRAS, BRAF in different cell lines